2007
DOI: 10.1080/13638490600822239
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-life: Child and parent perspectives following severe traumatic brain injury

Abstract: Children with TBI report significantly reduced QoL compared to a control group in the physical, psychological, cognitive and total score dimensions. However, TBI children with average academic performance (65%) obtained the same QoL scores as the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…For example, children with TBI who showed impaired ability to learn on a test of memory (CVLT-C) during their acute rehabilitation were more likely to have persistent problems at 1 and 2 years postinjury and were more likely to require special education services [Miller and Donders, 2003]. This is an important finding, as other studies have shown that children who maintain average academic performance with respect to their peers rated themselves and were rated by their parents as having a higher quality of life 4 years after injury, regardless of their level of physical limitations [Souza et al, 2007]. Taylor et al [2001] demonstrated a bidirectional relationship in family and child difficulties over time after pediatric TBI.…”
Section: Postinjury Predictors Traumatic Brain Injurymentioning
confidence: 72%
“…For example, children with TBI who showed impaired ability to learn on a test of memory (CVLT-C) during their acute rehabilitation were more likely to have persistent problems at 1 and 2 years postinjury and were more likely to require special education services [Miller and Donders, 2003]. This is an important finding, as other studies have shown that children who maintain average academic performance with respect to their peers rated themselves and were rated by their parents as having a higher quality of life 4 years after injury, regardless of their level of physical limitations [Souza et al, 2007]. Taylor et al [2001] demonstrated a bidirectional relationship in family and child difficulties over time after pediatric TBI.…”
Section: Postinjury Predictors Traumatic Brain Injurymentioning
confidence: 72%
“…By including only youth who were able to self-report responses for the PedsQL, the sample is biased towards individuals with greater cognitive ability. Some may argue that proxy-report is preferable to excluding individuals unable to self-report, however, given the reported discrepancies between proxy-and self-reported HRQOL, particularly in the psychosocial dimensions of HRQOL (Souza, Braga, Filho, & Dellatolas, 2007;Vami et al, 2006), it seems timely to use self-report. Due to the lack of norms for youth in Australia without disabilities, results were compared to norms for youth in the United States.…”
Section: Discussionmentioning
confidence: 97%
“…Present findings suggest that post-ABI adjustment in everyday living requires supports across a wide range of areas, particularly in IADL and psychosocial functioning domains, with 75-100% of children across the age groups of the present sample requiring supports in at least one of these areas. In addition, childhood ABI has been found to negatively affect family (parental) stress levels [48] and quality of life [49,50]. Family factors such as cultural background may also interact with the types and levels of support required.…”
Section: Concurrent Validitymentioning
confidence: 95%